If it's not what You are looking for type in the equation solver your own equation and let us solve it.
7(x+3)+4(x-1)=8
We move all terms to the left:
7(x+3)+4(x-1)-(8)=0
We multiply parentheses
7x+4x+21-4-8=0
We add all the numbers together, and all the variables
11x+9=0
We move all terms containing x to the left, all other terms to the right
11x=-9
x=-9/11
x=-9/11
| 1.3+.5x=-341 | | D/12d=6d+24 | | 7x-3+7x-3+5x+5x=36 | | 257=-u+180 | | 25=2x5 | | -25=4x=-5 | | 7x+3=-4x-19 | | 1/3x=-1/4x-10. | | 6+x=15x= | | 4y−2=22 | | 14=8-4x+22 | | -3(n-5)=(-9 | | 12=v/4+9 | | D=9/2(m-67) | | 49x+23=65 | | 28=4g-5+5 | | 12*n=-1 | | 10(x-12)=200 | | -3n(n-5)=(-9) | | -5×-16+3=8x-3 | | 6y+1=y-9 | | 5x-9=160 | | 34-3.8x=-5.8x | | 56+7y=14y | | 5x-13x-5x=-13 | | -91=6a+5(1+6a) | | 5x+17=8x-13 | | 4x+5=−3 | | 7/2+1/2x=41/2+9/2x | | 1x+125=180 | | -9+x=(x-3) | | -1/3x+15=6 |